Emission scenario model for regional air pollution - Karvosenoja, Niko (Finnish Environment Institute, 2013)
Air pollution emissions are produced in a wide variety of sources. They often result in detrimental impacts on both environments and human populations. To assess the emissions and impacts of air pollution, mathematical models have been developed. This study presents results from the application of an air pollution emission model, the Finnish Regional Emission Scenario (FRES) model, that covers the emissions of sulfur dioxide (SO2), nitrogen oxides (NOx), ammonia (NH3), non-methane volatile organic compounds (NMVOCs) and primary particulate matter (TSP, PM10, PM2.5 and PM1) in high 1 ´ 1 km2 spatial resolution over the area of Finland. The aims of the study were to identify key emission sources in Finland at present and in the future, to assess the effects of climate policies on air pollution, and to estimate emission reduction potentials and costs. Uncertainties in emission estimates were analyzed. Finally, emission model characteristics for use in different air pollution impact applications were discussed.The main emission sources in Finland are large industrial and energy production plants for SO2 (64% of 76 Gg a-1 total in the year 2000). Traffic vehicles are the main contributors for NOx (58% of 206 Gg a-1), NMVOCs (54% of 152 Gg a-1) and primary PM2.5 (26% of 31 Gg a-1) emissions. Agriculture is the key source for NH3 (97% of 33 Gg a-1). Other important sources are domestic wood combustion for primary PM2.5 (25%) and NMVOCs (12%), and fugitive dust emissions from traffic and other activities for primary PM10 (30% of 46 Gg a-1).In the future, the emissions of traffic vehicle exhaust will decrease considerably, by 76% (NMVOCs), 74% (primary PM2.5) and 60% (NOx), from 2000 to 2020, because of tightening emission legislations. Rather smaller decrease is anticipated in the emissions of large combustion plants, depending on future primary energy choices. Sources that are not subject to tight emission standards, e.g. domestic combustion and traffic-induced fugitive dust (i.e. non-exhaust), pose a risk for ...